(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article discusses the features of using interactive teaching methods in primary school. Their importance for the formation of cognitive activity, the development of communication skills and creative abilities of younger schoolchildren is emphasised. Particular attention is paid to the classification of interactive methods: game technologies, group work, discussion forms, project and research activities. Practical examples of the application of these methods in the classroom are provided, and their impact on the personal development of students is revealed